Performance of a Risk Analytic Tool (Index of Tissue Oxygen Delivery “IDO2”) in Pediatric Cardiac Intensive Care Unit of a Developing Country - Abbas, Qalab; Hussain, Muhammad Zaid H.; Shahbaz, Fatima Farrukh; Siddiqui, Naveed ur Rehman; Hasan, Babar S. (Frontiers in Pediatrics, 2022)
Objective: To determine the performance of a commercially available risk analytic tool (IDO2) to estimate the risk for SVO2<40% in patients admitted in cardiac intensive care unit (CICU) Methods: Medical and T3 records of all patients (aged 1 day to 12 years, weight >2kg) who received care in the CICU between October 1st, 2019, and October 1st, 2020, had SvO2 lab(s) drawn during CICU course and whose data was transmitted to T3, were included. The average IDO2 Index was computed in the 30-minute period immediately prior to each SvO2 measurement and used as a predictor score for SvO2 < 40%. Results: A total of 69 CICU admissions from 65 patients, median age 9.3 months (interquartile range 20.8) were identified. Surgical and medical patients were 61 (88%) and 8 (12%) respectively; 4 (5.7%) patients had single ventricle physiology. Tetralogy of Fallot n=23 (33.3%) and ventricular septal defects 17 (24.6%) were major cardiac diagnosis. 61 (89.9%) of the admissions were successfully discharged from the hospital. Of the 187-total included SvO2 labs, 17 (9%) were < 40%. The AUC of predicting SvO2 < 40% IDO2 was 0.87 (confidence interval (CI): 0.79-0.94). Average IDO2 above 75 had the highest absolute risk (42.11, CI: 20.25-66.50) and highest RR (4.63, CI: 2.31-9.28, p-value < 0.0001) of SvO2 < 40% Conclusion: IDO2 performed well in predicting low SvO2 (<40%) in pediatric patients presenting to a CICU in a low resource setting. Future work is needed to determine the effect of this predictive tool on clinical outcomes in such a setting.